Beyond Mastery: Interspecies Apprenticeship in Middle English Romance. (2nd January 2017) - Erwin, Bonnie J.
Abstract: Drawing upon Gala Argent's theory of interspecies apprenticeship, this article illuminates animal agency at work in several Middle English romances: Bevis of Hampton, Sir Gawain and the Green Knight, and two Fierabras romances. The extraordinary equine characters in these texts work to school their knights in chivalric virtues and behaviors, with horse often mastering human in a way that complicates traditional hierarchies ranking mankind above other creatures. Ultimately, this representation of horses contrasts with more anthropocentric discourses in other medieval genres: romances offer a unique way of recuperating a countervailing medieval perspective on animal agency, one that acknowledges animals as active participants in shaping human cultures.